Contemporary Investigation of Pvc Modified Bitumen - Thennarasu, R.; Tholkapiyan, M.; Ashok Ram, S. (International Journal of Engineering and Technology, 2026)
Bitumen is one of the most used binding materials in road pavement due to its excellent binding characteristics, waterproofing properties and low cost as compared to other binders. However, it is widely known to have various types of distresses and does not perform well in aggressive situations. To counter these shortcomings, bitumen is ordinarily assorted with various forms of modifiers such as polymers, crumb rubber, PVC, etc. Waste PVC that has been used previously as a part of sewerage system. In this project the waste PVC pipes which have been used as a modifier by an amount of 2%, 4% and 6% by weight of bitumen in making bituminous mixture for pavement applications. The different properties of PVC modified bitumen such as softening point, penetration value will be studied. In addition Brick powder is added as a filler to increase the absorption capacity and to increase the strength properties. Performance characteristics of the bituminous mix prepared by modified binder were also studied and compared with conventional bituminous mix. The results indicate that waste PVC pipe can be used efficiently in road construction. Flow and stability of the mix increase after incorporating PVC waste pipe. On the basis of experimental work it is concluded that the asphalt mixtures with waste PVC modifier can be used for flexible pavement construction.
Keywords: .